BMBE Law Public Information Campaign (BLPIC): A Strategic Communication Intervention Plan to Foster BMBE Law Awareness - Manipol, Vergel S. (Future Science / FSH-PH Publications, 2025)
The study proposes a Strategic Communication Plan